Process-induced warpage and stress estimation of through glass via embedded interposer carrier with ring-type framework. (February 2022) - Huang, Pei-Chen; Lin, Yu-Min; Liu, Hsing-Ning; Lee, Chang-Chun
Abstract: The feasibility of embedded interposer carrier (EIC) has been proposed and developed to improve the assembly process of three-dimensional (3D) integrated circuits (3D-ICs). However, the warpage and thermo-mechanical stress generated from the lamination process have been regarded as one of the critical issues in the mechanical reliability of 3D-ICs. A ring-type framework design was utilized in this study to conquer the warpage issue and improve the flatness of EIC, and its benefit was investigated by experimental measurement and process-oriented finite element simulation. Analytic results revealed that the warpage along diagonal and cross-sectional directions could be significantly restrained from 886 μm to 169 μm and from 484 μm to 84.6 μm, respectively. The maximum von Mises stress of Cu interconnect was observed to be 138 MPa simultaneously, and it did not generate plasticity after the lamination process. Consequently, the benefit of ring-type framework on the mechanical reliability of EIC architecture was investigated and discussed systemically. Graphical abstract: Unlabelled Image Highlights: Experimental measurement and process-oriented simulation were performed to investigate the EIC with metal ring. The warpage along the diagonal direction of EIC structure could be restrained by steel stiffener ring. Low-temperature lamination process integrated with stiffener ring improves warpage without sacrificing Cu trace reliability.